The Indonesian Constitutional Court and the Democratic Institutions in Judicial Review - Omara, Andy (The Constitutional Court of the Republic of Indonesia, 2017)
This paper focuses on the relationship between the Indonesian Constitutional Court, the legislature, and the executive in judicial review. It aims to explain the Court strategies in deciding judicial review cases related to the right to work in relation with the executive and the legislature. It appears that while constitutionally the Court is granted with a strong form of judicial review (as reflected in the finality of its decisions), it also employed other approaches in deciding cases related to the right to work. These approaches include the declaration of incompatibility, conditional decision, and the invalidation of a statute in its entirety. This paper argues that Katharine G. Youngâs typology of judicial review is quite helpful as an interpretive tool to understand the Court approaches when it decided cases related the right to work. The use of various approaches by the Court affected the relationship between the Court, the executive, and the legislature. This is because the executive and the legislature are the implementing agencies of the Court rulings.